Outcomes Associated With Extraction Versus Capping and Abandoning Pacing and Defibrillator Leads. Issue 15 (10th October 2017) - Pokorney, Sean D.; Mi, Xiaojuan; Lewis, Robert K.; Greiner, Melissa; Epstein, Laurence M.; Carrillo, Roger G.; Zeitler, Emily P.; Al-Khatib, Sana M.; Hegland, Donald D.; Piccini, Jonathan P.
Abstract : Background: Lead management is an increasingly important aspect of care in patients with cardiac implantable electronic devices; however, relatively little is known about long-term outcomes after capping and abandoning leads. Methods: Using the 5% Medicare sample, we identified patients with de novo cardiac implantable electronic device implantations between January 1, 2000, and December 31, 2013, and with a subsequent lead addition or extraction ≥12 months after the de novo implantation. Patients who underwent extraction for infection were excluded. Using multivariable Cox proportional hazards models, we compared cumulative incidence of all-cause mortality, device-related infection, device revision, and lead extraction at 1 and 5 years for the extraction versus the cap and abandon group. Results: Among 6859 patients, 1113 (16.2%) underwent extraction, whereas 5746 (83.8%) underwent capping and abandonment. Extraction patients tended to be younger (median, 78 versus 79 years; P <0.0001), were less likely to be male (65% versus 68%; P =0.05), and had shorter lead dwell time (median, 3.0 versus 4.0 years; P <0.0001) and fewer comorbidities. Over a median follow-up of 2.4 years (25th, 75th percentiles, 1.0, 4.3 years), the overall 1-year and 5-year cumulative incidence of mortality was 13.5% (95% confidence interval [CI], 12.7–14.4) and 54.3% (95% CI, 52.8–55.8), respectively. Extraction was associated with a lower risk of device infection at 5 years relative to capping (adjusted hazard ratio, 0.78; 95% CI, 0.62–0.97; P =0.027). There was no association between extraction and mortality, lead revision, or lead extraction at 5 years. Conclusions: Elective lead extraction for noninfectious indications had similar long-term survival to that for capping and abandoning leads in a Medicare population. However, extraction was associated with lower risk of device infections at 5 years. Abstract : Supplemental Digital Content is available in the text.